Review of Hybrid Finite Element – Statistical Energy Analysis methods in vehicle NVH predictions - Treszkai, Marcell Ferenc; Feszty, Dániel (Acta Technica Jaurinensis, 2019)
In the vehicle industry, the noise, vibration and harshness (NVH) characteristics of a car are becoming more and more important. In order to control these, it is necessary to know the sources and contributors to the interior noise level. This paper provide an overview of the state-of-the-art on predicting the NVH characteristics of fully trimmed vehicles in the mid-frequency gap between 400 Hz to 1 kHz. It is shown that for this frequency range, typically a hybrid FE-SEA method is used. This method provides a mixture of the advantages of the deterministic and statistical approaches. The first part of the paper introduces the method, followed by an overview of the different fields of usage in the vehicle industry. At the end of the paper, gaps in the knowledge are identified.